New Asmaradana in Indonesian contemporary poetry and Malayan pop song: product of rooted culture or new interpretations? - Suyitno, Suyitno (Penerbit Universiti Kebangsaan Malaysia, 2017)
Goenawan Mohamad, an Indonesian writer, created a poem called Asmaradana that is derived from the classic Asmaradana song written by Tandhakusuma. Comparing the two works gives the impression that these two texts interact dialectically in giving the concept of fate and love. The ‘new’ Asmaradana from Goenawan Mohamad is a soliloquy about realistic attitude in facing destiny whilst the ‘old’ Asmaradana is a kind of assertive reflection from the main character, Damarwulan, in responding to an inevitable situation. It generates new meanings and interpretations, whether it is from the writer or the reader, when a new work is created based on the classic ones. This paper examines how the new Asmaradana shows new interpretation compared to its previous versions; its prior texts. This paper discusses four Asmaradana poems, two of which are the re-made versions from Goenawan Mohamad and the Putri Gunung Ledang movie soundtrack, and how they are interrelated. This paper takes focus on the interpolations of meanings shown in contemporary works that are different from their originals. This paper shows that the new works still follow the tone of the original works but they create new interpretations.